Customer Satisfaction Act upon the Brand’s Fame: A Case Study of Nestle - Husna Aqila; Intan Syarmimi; Husna Adawiyah; Izzati Akhtar; Mohammed Sami Alhesainan; Loulwah Fahad Altayyar (International Journal of Applied Business and International Management, 2022)
Nestle is a globally recognized brand with a large following of dedicated customers because of its variety of products that captivate everyone who consumes it. This study aims to examine the correlation between customer satisfaction on Nestle’s fame and fortune. Nestle may have issues regarding their customer satisfaction which is affecting the company’s development. Therefore, this case study tries to show and analyze how Nestle meets customer satisfaction while improving its products. A survey has been carried out to obtain new, valid, and accurate data. A total of 100 respondents participated in this survey. Besides, secondary data for this study was acquired from a variety of resources such as websites, journals, and articles in order to gain a deeper understanding. The findings indicate that customer satisfaction influences the fame of Nestle. The findings also provide recommendations to enhance the opportunity of improving Nestle’s customer satisfaction and suggestions for future development.